2019
DOI: 10.1101/694935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption of prepulse inhibition is associated with severity of compulsive behavior and nucleus accumbens dopamine receptor changes in Sapap3 knockout mice

Abstract: Highlights• Disruption of PPI is associated with severity of compulsive grooming in Sapap3-KOs • D1 and D2/3 receptors in NAcC are negatively correlated with PPI and grooming • Chronic fluoxetine normalizes PPI and grooming • Therapeutic efficacy of fluoxetine on PPI correlates with attenuated DAT in NAc • NAc dopamine changes may underly severity of PPI in Sapap3-KOs Abbreviations CMS= centromedial striatum; DAT = Dopamine transporter; FLX= Fluoxetine; KOs = Knockout mice; NAc= nucleus accumbens; NAcC= NAc co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Taken together, we observe four distinct types of repetitive behaviours in the Sapap3 -/mouse model, two of which can unambiguously be described as of a tic-like nature. We confirm previously reported self-grooming sequences, which have been shown to adhere to a compulsive-like nature elsewhere (11,16). The in-between character of hindpaw scratching in the Sapap3 -/mouse most likely resembles hair-pulling or skin-picking described in OCD with grooming disorders or trichotillomania.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Taken together, we observe four distinct types of repetitive behaviours in the Sapap3 -/mouse model, two of which can unambiguously be described as of a tic-like nature. We confirm previously reported self-grooming sequences, which have been shown to adhere to a compulsive-like nature elsewhere (11,16). The in-between character of hindpaw scratching in the Sapap3 -/mouse most likely resembles hair-pulling or skin-picking described in OCD with grooming disorders or trichotillomania.…”
Section: Discussionsupporting
confidence: 89%
“…face and predictive validity suggest that the short grooming events fit with a ticlike repetitive behaviour while the long grooming events do not. Although undifferentiated into single-or multi-phase grooming events in all previous publications on the Sapap3 -/and other mouse models, self-grooming in general has been determined as compulsive-like behaviours through pharmacological characterization using the first-order treatment for obsessive-compulsive behaviours, fluoxetine, a selective serotonin reuptake inhibitor (SSRI) (11,16). Although previously never reported in the Sapap3 -/mouse model, the detection of comorbidity of tic-and compulsive-like elements in its self-grooming behaviour is in line with the numerous reports of comorbidity of tics and compulsions in OCD as well as TS patients (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical imaging studies revealed a reduction in D 2 receptor binding availability, which reflects low membrane expression of D 2 receptor and/or increased dopamine release, in the striatum of patients with OCD and substance use disorder (Denys et al, 2004;Fehr et al, 2008;Lee et al, 2009). Similar observations have also been reported in animal models of OCD and addiction (Nader et al, 2006;Manning et al, 2020). These observations raise the possibility that b -arrestin-mediated D 2 receptor internalization is facilitated in patients with compulsivity, supporting the present observation in QNP-sensitized mice.…”
Section: Discussionsupporting
confidence: 90%
“…Grooming is not classically considered to be a coping behavior in response to a stressor; animals will self-groom under low and/or high stress conditions (Kalueff et al, 2016;Smolinsky et al, 2009). However, animal models of obsessive-compulsive disorder (OCD) and Tourette Syndrome (TS) demonstrate high levels of repetitive self-grooming behavior (Manning et al, 2021;Nordstrom and Burton, 2002;Welch et al, 2007), and grooming can be elicited by central infusions of ACTH or DA agonists (Guild and Dunn, 1982;Taylor et al, 2010). The ACTH-induced grooming response was prevented by drugs that block DA receptors, while grooming induced by central ACTH infusion is augmented by the DA agonist apomorphine (Guild and Dunn, 1982).…”
Section: Discussionmentioning
confidence: 99%